(untitled) (Journal of Dhaka Medical College, 2024)
Background: The bleeding occurring proximal to the ligament of the treitz is known as Upper GI bleeding. The patient may present with hematemesis or melena. Upper gastrointestinal bleeding in children can result in complex and perhaps fatal clinical circumstances. It fluctuates significantly depending on changes in the patient’s demographics and other diseases. Methods: This was a cross sectional study conducted at the Department of Paediatrics, Dhaka Medical College Hospital, Dhaka. The study was conducted during the period of Jan’2020 to July 2022. The total number of study patients was 92. Result: The most extensive prevalence of UGIB is found in children aged 5 to 10 years (71.4%), followed by those aged 1 to 12 years (26.8%). Varices accounted for 67 (72.8%) of the UGIB causes, followed by erosive gastritis (6.5%), stomach ulcers (3.3%), esophagitis (2.2%), and Mallory Weiss tears (1.1%), with 13 (14.1%) of them being judged to be normal. Pallor was the most common presenting symptom, making up 82 (89.1%), then hematemesis 61(66.3%) and melena 30.4%, splenomegaly 55(59.8%), hematemesis plus melena (30.4%), hepatomegaly (28.3%), jaundice (15.6%), and melena (3.3%). Conclusion: Hematemesis is the most common presenting symptom of upper GI haemorrhage, which is more common in kids between the ages of 5 and 10. Esophageal varices were the most common source of intestinal bleeding. J Dhaka Med Coll. 2022; 31(2) : 215-219